2002
DOI: 10.1093/nar/30.7.e30
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Motorola CodeLinkTM microarray performance for gene expression profiling applications

Abstract: DNA microarrays enable users to obtain information on differences in transcript abundance on a massively parallel scale. Recently, however, data analyses have revealed potential pitfalls related to image acquisition, variability and misclassifications in replicate measurements, cross-hybridization and sensitivity limitations. We have generated a series of analytical tools to address the manufacturing, detection and data analysis components of a microarray experiment. Together, we have used these tools to optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
100
0
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 47 publications
21
100
0
2
Order By: Relevance
“…59 Overall, reproducibility test results were consistent with other acceptable published results. 55,60 Furthermore, array quality and specification for these studies were consistent with those described by Ramakrishnan et al 54 for this particular platform.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…59 Overall, reproducibility test results were consistent with other acceptable published results. 55,60 Furthermore, array quality and specification for these studies were consistent with those described by Ramakrishnan et al 54 for this particular platform.…”
Section: Discussionsupporting
confidence: 83%
“…This paper describes the use of this new oligonucleotide array in a biological validation study involving the treatment of rats with carbon tetrachloride (CCl 4 ), a well-established model of chemically induced hepatotoxicity. 9,11,12,52,53 The goal of this study was to show that this novel bioarray, which has already been demonstrated to meet or exceed current industry standards and specifications, 54 could be successfully employed to measure expected gene expression changes. It was hypothesized that the results of histopathological and gene expression analysis of hepatic tissue from CCl 4 -treated animals would confirm and/or reject previously published gene expression findings, as well as identify other target genes of interest, either not tested or missed by previously published studies that used other microarray platforms or more traditional methods of gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the RNA was processed as previously described (16,17). A reaction mix containing 5 mg of total RNA, bacterial RNA controls, 0.5 pmol/ml T7-(dT)24 oligonucleotide primers, and SuperscriptTM II reverse transcriptase (200 U/ml; Invitrogen, Carlsbad, CA) was incubated at 428C for 1 hour.…”
Section: Microarraymentioning
confidence: 99%
“…The present study utilized the CodeLink Bioarray Perfect system (GE Healthcare UK Ltd., Buckinghamshire, UK), which uses the UniSet Rat I Expression Bioarray that contains 9,028 gene probes, abbreviated hereafter as the 10K CodeLink array (11)(12)(13)(14). The 10K CodeLink array accommodates a broad range of genes derived from publicly available, well-annotated mRNA sequences.…”
Section: Gene Expression Bioarraysmentioning
confidence: 99%